Analisis Faktor-Faktor Yang Mempengaruhi KinerjaSistem Informasi Akuntansi(Studiempirispada dealer mobil yang ada di daerahSukoharjodan Surakarta) - Arif, Ikhwananto, Dr. Noer Sasongko, SE, M.Si (2015)
This study aimed to get empirical evidence using primary data, about the factors that affect the performance of the accounting information system at a car dealership in the area Sukoharjo and Surakarta. The sample used financial and administrative employee car dealer Toyota, Honda, Suzuki, Mazda, Kia, Hyundai, Isuzu, Mercedes, Tata, Hino, Nissan, Chevrolet and Mitsubishi in the area Sukoharjo and Surakarta, with purposive random sampling technique. Questionnaires were returned and processed a total of 44 questionnaires. Methods of testing instruments to test the validity of using the Pearson product moment correlation, while reliability was tested with Cronbach alpha. Data analysis techniques are used to test the hypothesis that includes multiple linear regression t test, F test, and test and R2. All the data acquired, processed with a software program SPSS for windows version 18.0 were first tested using the classical assumption that normality test, multicolinearity test, and test heterokedastisitas. In the validity and reliability tests indicate that all the items in the questionnaire statement for independent and dependent variables are valid and reliable. The classical assumption test showed that the data were normally distributed, while the results of the other classic assumption test shows that for all variables and heterokedastisitas free from multicollinearity. Regression models were generated good and unbiased. T test results showed that the variables of personal technical ability information system, top management support, and training and education programs have positive influence on the performance of the accounting information system, whereas for variable user involvement, the ability of formalization of information system development does not affect the performance of the accounting information system. Where the significance value of t for variable user engagement obtained t count of 0.196 with p = 0.846, variable engineering capability personalized obtained t count amounted to 2,699 with p = 0.010, variable top management support obtained t count amounted to 2,248 with p = 0,030, variable formalization of system development information obtained t count of -0.299, p = 0.767, variable training and education programs for acquired t count of 2,220 with p = 0.032. Keywords: User Involvement, Personal Technical Ability Information System, Top Management Support, a formalization of Information Systems Development, Education and Training Manual, Accounting Information System Performance.